2022
DOI: 10.3389/fphar.2022.1051103
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide promotes expansion of Nestin+ progenitor cells via Shh modulation and contributes to post-injury cerebellar replenishment

Abstract: Background: Regeneration of injuries occurring in the central nervous system is extremely difficult. Studies have shown that the developing cerebellum can be repopulated by a group of Nestin-expressing progenitors (NEPs) after irradiation injury, suggesting that modulating the mobilization of NEPs is beneficial to promoting nerve regeneration. To date, however, effect of exogenous pharmaceutical agonist on NEPs mobilization remains unknown. Parthenolide (PTL), a sesquiterpene lactone isolated from shoots of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Liu et al (2020b) observed that PTL increased the level of Bcl-2 and reduced the expression of BAX in Parkinson's disease rats [ 98 ]. Many studies have also confirmed that PTL can repair damaged nerves after nerve injury [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (2020b) observed that PTL increased the level of Bcl-2 and reduced the expression of BAX in Parkinson's disease rats [ 98 ]. Many studies have also confirmed that PTL can repair damaged nerves after nerve injury [ 99 , 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have demonstrated that cells expressing the proliferation marker nestin located in the cerebellum have been linked to the origin of medulloblastomas [ 140 ]. Other, more recent studies have revealed that the expansion of nestin-positive progenitors using pharmacological agents contributes to the replacement of damaged or lost cells after cerebellar injury [ 141 ]. However, it is clear that more work is needed to demonstrate neurogenesis in this area, especially if it is not associated with lesions.…”
Section: Neurogenesis In the Cerebellummentioning
confidence: 99%